Determinant Factors of Reading Difficulties Among First-Grade Students at MIN 1 Trenggalek - Septiningtyas, Reza; Kholis, Nur (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2023)
This research was conducted to find out more about the description of reading difficulties, as well as the factors that influence reading difficulties in grade 1 students. Out of all 112 grade 1 students, there are still 3 children whose reading skills still need attention. The three students still need full guidance in terms of reading besides their friends who are already able to read well. This study uses a qualitative research method with a case study approach. The data were obtained by conducting in-depth interviews with 3 subjects who were grade 1 students at MIN 1 Trenggalek. The data credibility test was carried out using the data source triangulation technique by conducting interviews with teachers and parents as well as observing students during class learning and using flashcard media. The results of the study show that students who experience reading difficulties are having difficulty spelling words, ignoring some syllables, finding it difficult to distinguish letters that are almost the same, pronouncing words that are not quite right, and not being able to write properly, still needing to point to the text being read, and still making mistakes in reading. pronounce letters. Reading difficulties are caused by internal factors and external factors. The internal factor is the lack of interest in learning to read caused by a less supportive mood. While external factors are learning methods that are not appropriate in previous education, lack of motivation from the family, especially parents, and lack of communication between teachers and parents.